PRIMARY HEALTHCARE POLICY IMPLEMENTATION IN PLATEAU STATE, NIGERIA, 1990-2010 (2015)
Healthcare policy initiatives have often failed to achieve the set goal of providing access to basic health services in Nigeria. Although implementation studies have sought to explain healthcare policy at both the international and national levels, few studies have focused at the sub-national level of the states and local governments (LGs). Also, the few studies on Plateau State healthcare delivery have been done largely by donor agencies with limited focus on political economy of healthcare policy and primary healthcare (PHC) delivery. This study, therefore, examined the implementation of PHC policy in Plateau State from a political economy perspective, from 1990 to 2010. Political Economy provided the theoretical basis. The study adopted survey and case study research designs. Using a two-stage random sampling method, 903 households from 12 health districts drawn proportionately, covering rural and urban populations of the state, responded to copies of a user-based questionnaire. The questionnaire focused on socio-demographic characteristics (age, sex and education), healthcare financing, provision and utilisation of health services and management variables. Thirty key informant interviews were conducted with key government officials, past and current commissioners for health, LGs’ chairmen and traditional birth attendants. Secondary data were sourced on policy achievement indicators from the Plateau State Health Strategic Plan 2010, National Bureau of Statistics: Annual Abstract of Statistics and Statistical fact sheet. Fund, human resources, health facility ratio, quality of service, under-5 mortality, community participation/stakeholder frameworks, and political/bureaucratic commitment were variables used for the analysis. Quantitative data were analysed, using descriptive and regression statistics at p<0.5 level of significance and qualitative data were content analysed. Respondents’ age was 43.1 ± 13.3 years and 55.5% were females while those with secondary and post-secondary education constituted 70.5% and 17.6% had primary education. There was no significant difference in the type of services rendered and the quality of services provided (F value = 33.318). Majority of respondents (80%) indicated poor quality services. The health sector was poorly funded with an average budget of 6% and 1% per annum at the state and LG levels respectively. High cost of medical services forced the rural populace to patronise quack chemists and traditional healers. There were 327 nurses/midwives in 908 PHCs across the LGs in the state, a ratio of 0.3/PHC against the minimum 4/facility national standard. Healthcare professional ratio was 1.4/1,000 population compared to national standard of 2/1,000, and World Health Organisation standard of 2.5/1000. Under-5 mortality was at an average of 2.6%. Poor community participation resulted from lack of clearly-stated roles and responsibilities and lack of clear guidelines for collaboration among stakeholders. Decentralised healthcare givers were not empowered to take decisions that can enhance their performance. Poor attitude to work, corruption and ineffective accountability weighed heavily on implementation. The objectives of the primary healthcare policy were not fully achieved due to poor implementation. Policy action deviated from policy intention because of lack of commitment, limited fund and unclear guidelines for collaboration and participation and therefore resulting in performance and interaction deficits among stakeholders